The Influence Of Asset Management, Green Accounting, And Social Disclosure On Financial Performance In The Manufacturing Sector Listed On The IDX - Kedong, Susana Lise; Dura, Justita (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives: This study explores the impact of asset management, green accounting, and social disclosure on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange (IDX) between 2022 and 2024. These factors are increasingly relevant as firms seek to improve profitability while maintaining sustainability in a competitive market. Background Problems: The research addresses the question: Do asset management, green accounting, and social disclosure significantly influence the financial performance of IDX-listed manufacturing companies? Research Methods: A quantitative explanatory design was adopted, utilizing secondary data from annual reports and PROPER environmental ratings. A purposive sample of 29 manufacturing firms was selected for the 2022–2024 period. Multiple linear regression analysis was performed using SPSS version 26 to test the hypotheses. Finding/Results: The results reveal that asset management and green accounting have a positive and significant effect on financial performance, whereas social disclosure shows no direct impact. This indicates that efficient resource utilization and systematic adoption of green accounting practices contribute to profitability, while social disclosure alone does not guarantee financial improvement. Conclusion: The study concludes that companies should prioritize optimal asset management and integrate green accounting into their operations to enhance competitiveness and firm value. Future research is recommended to examine potential mediating factors such as corporate governance and stakeholder engagement to better understand the role of social disclosure in financial outcomes.